Learning with artificial intelligence - Hayes, Christian (New York, New York 3G E-Learning LLC, 2025)
This book aims to cover the transformative impact of AI on education, exploring both its potential benefits and the challenges it presents. It aims to provide a comprehensive understanding of how AI technologies are being integrated into educational settings, the pedagogical shifts the necessitate, and the ethical considerations they entail. Through a blend theoretical discussions, practical applications, and case studies, this book serves as a guide for educators, policymakers, and technologists seeking to harness the power of AI to enhance learning and teaching.
Includes bibliographical references and index.
Keywords: Artificial intelligence; Artificial intelligence--History.